2019
DOI: 10.31629/intek.v3i2.1360
|View full text |Cite
|
Sign up to set email alerts
|

Skrining Komponen Bioaktif Ethanol 96% Sargassum sp. sebagai Antibakteri Terhadap Vibrio Harveyi

Abstract: Skrining Komponen Bioaktif Ethanol 96% Sargassum sp. sebagai Antibakteri Terhadap Vibrio Harveyi. Alga cokelat (Sargassum sp.) yang digunakan dalam penelitian ini di peroleh dari sepanjang Garis Pantai Trikora Pulau Bintan, Kepulauan Riau. Yang dimaserasi menggunakan pelarut etanol 96% untuk melihat senyawa bioaktif yang terkandung pada sampel kemudian dilakukan uji aktivitas antibakteri terhadap bakteri vibrio harveyi. Penelitian ini bertujuan untuk mengetahui komponen senyawa bioa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…sebesar 2.7%. 14 Menurut Puji et al hasil rendemen yang ditarik oleh pelarut bergantung pada kadar air total yang masih terikat pada sampel. 15 Semakin sedikit total kandungan air maka semakin tinggi kandungan rendemen yang didapatkan.…”
Section: Rendemen Ekstrak Kental Dan Fraksiunclassified
“…sebesar 2.7%. 14 Menurut Puji et al hasil rendemen yang ditarik oleh pelarut bergantung pada kadar air total yang masih terikat pada sampel. 15 Semakin sedikit total kandungan air maka semakin tinggi kandungan rendemen yang didapatkan.…”
Section: Rendemen Ekstrak Kental Dan Fraksiunclassified
“…The yield quantity depended on the total moisture content of the samples. The less water content, the greater the yield obtained (Naina et al, 2019). According to previous study, ethyl acetate extract of S. cinereum showed the percentage of the yield was 0.47% (Alamsjah et al, 2014), and S. polycystum had the yield percentage as much as 0.91% (Savitri et al, 2017).…”
Section: Antibacterial Activitymentioning
confidence: 90%
“…Research conducted shows that antibacterial activity is bacteriostatic, that an antimicrobial is bacteriostatic if the antimicrobial compound is only able to inhibit bacterial growth if the administration of the compound continues to be carried out and if it is stopped or exhausted, the growth and propagation of the bacteria will increase again which is characterized by a decrease in the diameter of the resistance zone [18]. The results of the study [19] showed that the mechanism of action of the antibacterial compound Sargassum sp. it is suspected by disrupting the peptidoglycan component in bacterial cells, so that the layers of the cell wall are not formed intact and cause the death of these cells.…”
Section: Nomentioning
confidence: 99%